2022
DOI: 10.1038/s41598-022-12178-5
|View full text |Cite
|
Sign up to set email alerts
|

Delayed processing of blood samples impairs the accuracy of mRNA-based biomarkers

Abstract: The transcriptome of peripheral white blood cells (PWBCs) are indicators of an organism’s physiological state, thus making them a prime biological sample for mRNA-based biomarker discovery. Here, we designed an experiment to evaluate the impact of delayed processing of whole blood samples on gene transcript abundance in PWBCs. We hypothesized that storing blood samples for 24 h at 4 °C would cause RNA degradation resulting in altered transcriptome profiles. There were no statistical differences in RNA quality … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…We observed that there was a difference in median scores between the stored and the fresh samples, probably due to RNA degradation in biobanked samples. 29 However, by recentring the means of the biobanked samples to the prospective samples, we found a similar distribution of scores between the two groups and the calculated AUCs were almost identical. This batch effect difference between stored and fresh samples could have been suboptimal for analysis of diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 55%
“…We observed that there was a difference in median scores between the stored and the fresh samples, probably due to RNA degradation in biobanked samples. 29 However, by recentring the means of the biobanked samples to the prospective samples, we found a similar distribution of scores between the two groups and the calculated AUCs were almost identical. This batch effect difference between stored and fresh samples could have been suboptimal for analysis of diagnostic accuracy.…”
Section: Discussionmentioning
confidence: 55%
“…We obtained 30 and 36 libraries produced from samples collected from males [GSE176219 ( Rabaglino et al, 2021 ), GSE196974 ( Rabaglino et al, 2021 ), GSE128075 ( Fang et al, 2020 )] and females [GSE55435 ( Canovas et al, 2014 ), GSE192530 ( Wilson et al, 2022 )], respectively, from the GEO public database. On average, after filtering, there were 48,700,745, and 17,829,956 fragments mapped to the reference cattle genome and chromosome Y for females and males, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We used public RNA-sequencing datasets produced from samples obtained from male or female cattle. Datasets from females [GSE55435 ( Canovas et al, 2014 ), GSE192530 ( Wilson et al, 2022 )] contained samples from the endometrium, fat, hypothalamus, liver, muscle, ovary, pituitary, peripheral white blood cells, and uterus. Datasets from males [GSE176219 ( Rabaglino et al, 2021 ), GSE196974 ( Rabaglino et al, 2021 ), GSE128075 ( Fang et al, 2020 )] contained epididymis, liver, muscle, prostate, and testis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We processed the blood samples following processes described elsewhere [39, 40, 43] within three hours of sampling [43]. Tubes containing whole blood samples were centrifuged for 25 minutes (min) at 4°C and 2,000x g to separate the buffy coat.…”
Section: Methodsmentioning
confidence: 99%